2019 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW) 2019
DOI: 10.1109/eurospw.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Discharged Payment Channels: Quantifying the Lightning Network's Resilience to Topology-Based Attacks

Abstract: The Lightning Network is the most widely used payment channel network (PCN) to date, making it an attractive attack surface for adversaries. In this paper, we analyze the Lightning Network's PCN topology and investigate its resilience towards random failures and targeted attacks. In particular, we introduce the notions of channel exhaustion and node isolation attacks and show that the Lightning Network is susceptible to these attacks. In a preliminary analysis, we confirm that the Lightning Network can be clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 24 publications
(36 reference statements)
6
60
1
8
Order By: Relevance
“…Dynamically generated wealth inequalities and concentration may be detected by means of centrality measures. • The resilience of the network can be studied under different types of attacks and compared with available empirical results 7,11 . • Different choices of the kernel f(x, y) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamically generated wealth inequalities and concentration may be detected by means of centrality measures. • The resilience of the network can be studied under different types of attacks and compared with available empirical results 7,11 . • Different choices of the kernel f(x, y) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…• The resilience of the network can be studied under different types of attacks and compared with available empirical results [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…on the system resilience by monitoring when the original network is broken into multiple isolated clusters [8][9][10]. In the Lightning Network case, it has been shown that some types of targeted attacks -aimed at consuming, for instance, the channels' liquidity of specific nodes -may yield severe consequences for the resilience of the network in terms of average payment flow and reachability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have already analyzed security and privacy concerns in offchain networks. Rohrer et al [24] focus on channel-based attacks and proposes methods to exhaust a victim's channels via malicious routing (up to potentially total isolation from the victim's neighbors) and to deny service to a victim via malicious HTLC construction. Tochner et al [27] propose a denial of service attack by creating low-fee channels to other nodes, which are then naturally used to route payments for fee-minimizing network participants and then dropping the payment packets, therefore forcing the sender to await the expiration of the already set-up HTLCs.…”
Section: Related Workmentioning
confidence: 99%